The Influence of Socio-Economic Factors on Public Interest in Cash Waq - Lubis, Nasrul Kahfi; Azhar, Iqlima (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to analyze the influence of socio-economic factors on public interest in cash waqf participation in Indonesia. Using primary data from a national survey of 500 respondents, multiple linear regression analysis was conducted to examine the relationship between socio-economic variables and interest in cash waqf. The dependent variable is public interest in cash waqf, measured on a Likert scale (1-5), while the independent variables include income, education level, age, knowledge of cash waqf, trust in waqf institutions, and location (urban vs. rural). The results show that income (β = 0.250, p < 0.01), knowledge of cash waqf (β = 0.380, p < 0.01), and trust in waqf institutions (β = 0.180, p < 0.05) have a significant positive effect on interest in cash waqf. In contrast, age has a significant negative effect (β = -0.120, p < 0.05), indicating that younger individuals are more interested in cash waqf. Location also plays a significant role, with urban residents showing higher interest than rural residents (β = 0.150, p < 0.05). However, education level does not significantly influence interest in cash waqf (p = 0.230). The regression model explains 58% of the variation in interest in cash waqf (R² = 0.580). These findings suggest that increasing public knowledge, building trust in waqf institutions, and targeting younger and urban populations can enhance participation in cash waqf. This study provides practical recommendations for policymakers and waqf institutions to promote cash waqf as a tool for sustainable social finance.